Предмет: Математика, автор: vanakicun2

-8(2х-3)+13 = 42-(9х+18)


хелп срочно даю Макс балов​

Ответы

Автор ответа: olegandrejcenko846
0

Ответ:

x=13/7

Пошаговое объяснение:

-8(2x+3)+13=42-(9x+18)

-16x+24+13=42-9x-18

-16x+9x=42-18-24-13

-7x=-13

7x=13

x=13/7

Проверка

-8((26/7)-3)+13=42-(9*(13/7)+18)

-29,7+24+13=42-16,7-18

7,3=7,3

7,3-7,3=0

0=0

Ответ: x=13/7

Автор ответа: iramazurk
0

Пошаговое объяснение:

-8(2х - 3) + 13 = 42 - (9х + 18)

-16х + 24 + 13 = 42 - 9х - 18

-16х + 37 = 24 - 9х

-16х + 9х = 24 - 37

-7х = -13

х = -13 : (-7)

х = 13/7

х = 1 6/7

Похожие вопросы
Предмет: Математика, автор: alish56